Las teorías del desarrollo al desarrollo sustentable - Coronado Ramírez, José Luis (Frontera Norte, 2017)
Esthela Gutiérrez Garza y Édgar González Gaudiano, México, Siglo xxi Editores/Universidad Autónoma de Nuevo León, 216 pp.